STRATEGI PEMASARAN BAWANG MERAH (ALIUM ASCALONICUM L) DI KEBUN PRAKTEK FAKULTAS TEKNOLOGI PANGAN PERTANIAN DAN PERIKANAN UNIVERSITAS NUSA NIPA - Dainu, Donatus; Selvi Irawati Kwuta, Magdalena; Nong, Fiator (Jurnal Biogenerasi, 2025)
Marketing strategy is one way to introduce products to consumers, this is important because it will be related to the profits that the company will achieve. Marketing strategies will be optimally useful if supported by structured planning both internally and externally to the company. This research used 15 interview samples taken from those in charge of the garden, garden employees, observers of related organic plants and general buyers. The interview results were processed using the purposive sampling method and SWOT analysis.The research results show that: 1) based on the IFAS and EFAS matrices, the IFAS score is 3.05 which is located in the strength quadrant and EFE is 2.80 which is located in quadrant I (growth). The strategy implemented in this condition is to support growth policies the aggressive one. 2) increase the quantity and quality of production to meet the high demand for shallots and develop quality onion products with farming locations near markets.